Formaldehyde emission in wood based panels: effect of curing reactions. (August 2014) - Costa, N. A.; Pereira, J.; Ferra, J.; Cruz, P.; Martins, J.; Magalhães, F. D.; Mendes, A.; Carvalho, L. H.
<x content-type="archive" xml:space="preserve">Abstract</x> The influence of hexamine formed as byproduct during the UF cure was ignored in the past. However, with the increasing interest on low formaldehyde emission boards, this issue has become more pertinent. Formaldehyde release from hexamine degradation is extensive and could limit the success of the development of low formaldehyde emission adhesives if the conventional latent catalysts remain in use. In this study, formaldehyde released from recycled wood, hexamine and cured UF resin was assessed. Citric and oxalic acid, in solid form, were used as catalysts for UF resin in the production of particleboard. Mats with solid acids are less susceptible to resin pre-cure than with a latent catalyst. However, they can have higher formaldehyde emissions than latent catalyst. When both catalysts were used, combined with an ultra-low formaldehyde to urea molar ratio resin the internal bond was improved and formaldehyde content was below 4 mg per 100 g of oven dry board.